2023
DOI: 10.1021/acs.jpcc.3c00769
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Transfer-Induced Enhanced Valley Splitting of Excitonic Emission of Inorganic CdTe@ZnS QDs in the Presence of Organic J-Aggregates: A Spectroscopic Insight into the Efficient Exciton (Inorganic)–Exciton (Organic) Coupling

Abstract: An inorganic−organic nanohybrid material comprising an inorganic exciton (CdTe@ZnS) and an organic exciton (Jaggregates) has been synthesized, and subsequently investigations on exciton−exciton coupling between two components of the materials are carried out by employing various spectroscopic techniques. Analysis of the data has revealed very high Forster-type resonance energy transfer (FRET) from the donor quantum dots (QDs) to the acceptor J-aggregates. Interestingly, a clear splitting of the QD emission ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The UV‐Vis absorption profiles of the products derived from Zn(CH 3 COO) 2 and sodium sulfide exhibit two absorption peaks within the UV range. Prior research utilized density functional theory to analyze the electronic states of the ZnS structure, suggesting that the band‐edge absorption could originate from either the inorganic or organic component, both contributing to a blue shift in the absorption spectra [55,56] . Notably, a broad excitonic peak emerges at 330 nm, gradually sharpening and shifting to 282 nm [57] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UV‐Vis absorption profiles of the products derived from Zn(CH 3 COO) 2 and sodium sulfide exhibit two absorption peaks within the UV range. Prior research utilized density functional theory to analyze the electronic states of the ZnS structure, suggesting that the band‐edge absorption could originate from either the inorganic or organic component, both contributing to a blue shift in the absorption spectra [55,56] . Notably, a broad excitonic peak emerges at 330 nm, gradually sharpening and shifting to 282 nm [57] .…”
Section: Resultsmentioning
confidence: 99%
“…Prior research utilized density functional theory to analyze the electronic states of the ZnS structure, suggesting that the band-edge absorption could originate from either the inorganic or organic component, both contributing to a blue shift in the absorption spectra. [55,56] Notably, a broad excitonic peak emerges at 330 nm, gradually sharpening and shifting to 282 nm. [57] Comparatively, the excitonic absorption peak positions in the absorption spectra of the prepared nanostructures exhibit a slight blue shift when compared to the bulk ZnS value (334 nm).…”
Section: Uv-visible Spectral Analysismentioning
confidence: 99%
“…The position of the valley splitting or the quenching dip of the DHN emission in the presence of Cyt c appears exactly at the Soret band absorption peak position (at 409 nm) of Cyt c. Therefore, the Cyt c induced unique quenching feature of the DHN emission can be attributed to the strong binding (Figure b) assisted efficient Förster resonance energy transfer (FRET) between the DHN photosensitizer donors and the heme center of the Cyt c acceptor. Chakraborty et al have recently observed FRET assisted valley splitting on the excitonic emission spectrum of an inorganic quantum dot by an organic dye forming J-aggregates . Choi et al earlier reported plasmon resonance energy-transfer-based quenching dips on the plasmon band of Au nanoparticles in the presence of Cyt c. They utilized this quenching dip for molecular imaging of Cyt c in living cells. , However, these detection techniques are based on absorption spectroscopy (relatively less sensitive than fluorescence spectroscopy) and are highly affected by the variation in surface charge, size, and morphology of the nanoparticles .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Chakraborty excitonic emission spectrum of an inorganic quantum dot by an organic dye forming J-aggregates. 42 Choi et al earlier reported plasmon resonance energy-transfer-based quenching dips on the plasmon band of Au nanoparticles in the presence of Cyt c. They utilized this quenching dip for molecular imaging of Cyt c in living cells. 43,44 However, these detection techniques are based on absorption spectroscopy (relatively less sensitive than fluorescence spectroscopy) and are highly affected by the variation in surface charge, size, and morphology of the nanoparticles.…”
Section: Spectral Valley Splitting and Quantized Quenching Dip Of The...mentioning
confidence: 99%
“…Cy3 and C5 molecules usually act as a pair of donors and acceptors in Förster or fluorescence resonance energy transfer (FRET). , The close distance and spectral overlap of two dye molecules lead to a transfer of excitations from Cy3 donors to Cy5 acceptors. Here, Cy3 insertion results in a large TPL enhancement without a new emission band, indicating that a highly efficient FRET effect occurred in the Cy5/Cy3/Ag hybrids.…”
Section: Resultsmentioning
confidence: 99%